Analysis of mental workload during exams in hybrid learning in the new normal era post-pandemic - Yadi, Yayan Harry; Umyati, Ani; Mariawati, Ade Sri; Lady, Lovely; Dewantari, Nustin Merdiana; Herlina, Lely; Alvizar, Rezi (Universitas Sultan Ageng Tirtayasa, 2025)
During the Covid-19 pandemic, most universities implemented distance learning to prevent the spread of the virus. After the pandemic, the learning process shifted to a hybrid method, combining both offline and online instruction. This hybrid system is applied to certain courses, featuring face-to-face classroom sessions alongside video conferencing for lectures. However, the hybrid learning approach has led to a decline in the student achievement index for some students, highlighting the need to evaluate their mental workload. Therefore, this study aimed to measure students’ mental workload during both online and offline exams using the NASA Task Load Index (NASA-TLX) method. The results showed a higher average mental workload score for offline exams compared to online exams. Statistical analysis revealed a significant difference between the scores, indicating a notable disparity in mental workload between offline and online exams. In conclusion, the mental workload associated with hybrid learning—particularly during exams—is considered high.